Should early amputation impact initial fluid therapy algorithms in burns resuscitation? A retrospective analysis using 3D modelling. Issue 1 (8th June 2016) - Staruch, Robert M T; Beverly, A; Lewis, D; Wilson, Y; Martin, N
Abstract : Aims: While the epidemiology of amputations in patients with burns has been investigated previously, the effect of an amputation on burn size and its impact on fluid management have not been considered in the literature. Fluid resuscitation volumes are based on the percentage of the total body surface area (%TBSA) burned calculated during the primary survey. There is currently no consensus as to whether the fluid volumes should be recalculated after an amputation to compensate for the new body surface area. The aim of this study was to model the impact of an amputation on burn size and predicted fluid requirement. Methods: A retrospective search was performed of the database at the Queen Elizabeth Hospital Birmingham Regional Burns Centre to identify all patients who had required an early amputation as a result of their burn injury. The search identified 10 patients over a 3-year period. Burn injuries were then mapped using 3D modelling software. BurnCase3D is a computer program that allows accurate plotting of burn injuries on a digital mannequin adjusted for height and weight. Theoretical fluid requirements were then calculated using the Parkland formula for the first 24 h, and Herndon formula for the second 24 h, taking into consideration the effects of the amputation on residual burn size. Results and conclusions: This study demonstrated that amputation can have an unpredictable effect on burn size that results in a significant deviation from predicted fluid resuscitation volumes. This discrepancy in fluid estimation may cause iatrogenic complications due to over-resuscitation in burn-injured casualties. Combining a more accurate estimation of postamputation burn size with goal-directed fluid therapy during the resuscitation phase should enable burn care teams to optimise patient outcomes.